A miR-129-5P/ARID3A Negative Feedback Loop Modulates Diffuse Large B Cell Lymphoma Progression and Immune Evasion Through Regulating the PD-1/PD-L1 Checkpoint - Zheng, Weili; Lai, Guilan; Lin, Qiaochu; Issah, Mohammed Awal; Fu, Haiying; Shen, Jianzhen (Frontiers in Cell and Developmental Biology, 2021)
The activated B cell (ABC) and germinal center B cell (GCB) subtypes of diffuse large B cell lymphoma (DLBCL) have different gene expression profiles and clinical outcomes, and miRNAs have been reported to play important roles in tumorigenesis, progression, and metastasis. This study aimed to explore the differentially expressed miRNAs and target genes in the two main subtypes of DLBCL. Hub miRNAs were identified by constructing a regulatory network, and in vitro experiments and peripheral blood samples of DLBCL were used to explore the functions and mechanisms of differential miRNAs and mRNAs. Differentially expressed miRNAs and genes associated with the two DLBCL subtypes were identified using GEO datasets. Weighted gene co-expression network analysis shows that one gene module was associated with a better prognosis of patients with the GCB subtype. Through the construction of a regulatory network and qPCR verification of clinical samples and cell lines, miR-129-5p was identified as an important differential miRNA between the ABC and GCB subtypes. The negative relationship between miR-129-5p and ARID3A in DLBCL was confirmed using luciferase reporter assays. Overexpression of miR-129-5p and knockdown of ARID3A inhibited the proliferation of SU-DHL-2 (ABC-type) cells and promoted their apoptosis through the JAK and STAT6 signaling pathways. In addition, inhibition of miR-129-5p and overexpression of ARID3A promoted the proliferation and reduced apoptosis of DB (GCB-type) cells. Inhibition of miR-129-5p and overexpression of ARID3A in DB promoted immune escape by increasing PD-L1 expression, which was transcriptionally activated by ARID3A. In conclusion, we showed for the first time that the mir-129-5P/ARID3A negative feedback loop modulates DLBCL progression and immune evasion by regulating PD-1/PD-L1.